Philosophical foundations and their implications on the Islamic education - Rahimah, Embong; Fatimah Zaharah, Ismail; Mohd Taufiq, Abd. Talib; Mohd Ridhuan Tee, Abdullah; Mariam Nabilah, Mohd Noor; Raja Hazirah, Raja Sulaiman (2017)
This paper aims to elucidate some philosophical foundations underlying education in the Islamic weltanschauung. The qualitative method of philosophical analysis is employed for the purpose of this study. The finding of this study is the significance of four philosophical foundations, namely, the ontological, epistemological, theological and axiological, which are essential for developing a theoretical framework for Islamic education. The ontological foundation, which pertains to the theory of existence or being, focusses on human nature and man's integrative components and functions. The epistemological foundation illuminates the nature of knowledge, its sources and methodologies. The theological foundation constructs the Islamic belief system based on the unity of Divinity and the tawhidic paradigm. The fourth foundation is the axiological, which emphasises certain key values underlying the Islamic value system. This study has some implications on Islamic education. The ontological foundation strengthens the philosophical basis of Islamic education, while the epistemological foundation provides curricular implications on its content and both the theological and axiological foundations are significant for the methodological processes of education. Together, they ensure a holistic personality as the final product of Islamic education.